Shall we share? A repository for Open Research Data in agriculture and environmental sciences1. (22nd June 2015) - Abbà, S.; Birello, G.; Vallino, M.; Perin, A.; Ghignone, S.; Caciagli, P.
<x xml:space="preserve">Abstract</x> Many initiatives actively encourage investigators to make their research data available, but the process of sharing data is perceived by most researchers more as a burden than as a chance to increase the visibility of their results and improve the value of their research. One of the main barriers to open research data (ORD) is the need for interoperable data e‐infrastructures that allow researchers to manage a whole scientific information life cycle and a variety of stakeholders from different sectors to retrieve and exploit these data. In the pilot project presented in this study an open access and open source repository was developed to store, preserve and make accessible heterogeneous agricultural ORD collected over decades of scientific research about plant‐microbe interactions, with a particular focus on plant virus disease symptoms. Additionally, a step‐by‐step installation guide to set up a repository and simple operating procedures for data stewardship were provided.